2005
DOI: 10.1016/j.susc.2005.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and molecular adsorption on Pt(111)

Abstract: The adsorption of several atomic (H, O, N, S, and C) and molecular (N 2 , HCN, CO, NO, and NH 3 ) species and molecular fragments (CN, CNH 2 , NH 2, NH, CH 3 , CH 2 , CH, HNO, NOH, and OH) on the (1 1 1) facet of platinum, an important industrial and fuel cell catalyst, was studied using self-consistent periodic density functional theory (DFT-GGA) calculations at a coverage of 1/4 ML. The best binding site, energy, and position, as well as an estimated diffusion barrier, of each species were determined. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
217
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(272 citation statements)
references
References 94 publications
(155 reference statements)
52
217
3
Order By: Relevance
“…On the other hand, the frequency of the Pt-H stretching mode is not affected: The trajectory of the adsorbate in the interval 5.5 -5.9 ps, during which it stays at an atop site, yields 2286 cm À1 for the Pt-H stretching mode; the deuteron to proton isotope factor, 1.41, was taken into account to obtain the frequency. The frequency is almost the same as that for Pt (111) lation 27) and is comparable with the experimentally measured frequency. 28) The Pt-H vibration and the potential surface for H-diffusion are thus affected differently by the water.…”
Section: Electron Transfer and Surface Diffusionsupporting
confidence: 86%
“…On the other hand, the frequency of the Pt-H stretching mode is not affected: The trajectory of the adsorbate in the interval 5.5 -5.9 ps, during which it stays at an atop site, yields 2286 cm À1 for the Pt-H stretching mode; the deuteron to proton isotope factor, 1.41, was taken into account to obtain the frequency. The frequency is almost the same as that for Pt (111) lation 27) and is comparable with the experimentally measured frequency. 28) The Pt-H vibration and the potential surface for H-diffusion are thus affected differently by the water.…”
Section: Electron Transfer and Surface Diffusionsupporting
confidence: 86%
“…We have previously shown that at these conditions methionine decomposes to SCH 3 moieties that bind to the Pd catalyst, but that it does not decompose completely to yield atomic sulfur [19]. In contrast, the fractional uptake observed on Pt and Ni is consistent with the saturation coverage by atomic sulfur on the close-packed facets of each metal [35,36]. These results, then, are suggestive of the decomposition of methionine to form atomic sulfur on Pt and Ni.…”
Section: Discussionmentioning
confidence: 76%
“…The next step is to estimate values of binding energies for adsorption of all species on the surface, for example using experimental results from the literature, results from DFT calculations, or scaling relations (20)(21)(22)(23)(24). In addition, it is necessary to estimate values for the entropies of the adsorbed species, for example using results from experimental studies (25), correlations in the literature (26), results from DFT calculations of vibrational frequencies (27)(28)(29)(30)(31)(32)(33)(34), combined with hindered translator and hindered rotor models for the three modes associated with motion parallel to the surface (35,36), or by assuming models for the extent of mobility on the surface. It is now possible to estimate values for lumped equilibrium constants, K ads,i , to form the adsorbed species from the reactants and/or products, followed by calculation of θ p .…”
Section: Analytical Strategy For Analysis Of Reaction Schemesmentioning
confidence: 99%